Association of Anti-Coxsackie Virus-B IgG with Autoantibodies Related to Type 1 Diabetes Mellitus (Iraqi Journal of Medical Sciences, 2022)
Background: Coxsackievirus B is a virus may cause type 1 diabetes. There are links between Coxsackievirus B infections and type 1 diabetes. The presence of autoantibodies in pancreatic beta cells has been linked to the development of type 1 diabetes following Coxsackievirus B infection.Objective: To detect autoantibodies in patients with type 1 diabetes. Also, to find if there is an association between pancreatic beta cell autoantibodies and Coxsackievirus-B IgG.Methods: This study was done from January to March 2021, it included two groups of 75 children; their ages ranged from one month to fifteen years. Children with type 1 diabetes were admitted to the diabetic and endocrine glands center in Thi-Qar governorate, whereas children without diabetes (control group) were admitted to Bint Al-Huda Children's Hospital in Nasiriyah/Thi-Qar. Venous blood was taken from each person for estimation of random blood sugar, serum fructosamine, and HbA1c in the laboratory of the diabetic and endocrine glands center. Pancreatic beta cell autoantibodies and anti-Coxsackievirus-B IgG was detected by enzyme-linked immunosorbent assay. The statistical analyses were done using SPSS 25. The study population P-values below 0.05 to be statistically significant. The study was authorized by Al-Nahrain University's Institutional Review Board and parental consent was taken.Results: The patients had significantly greater levels of random blood sugar, fructosamine, and HbA1c than healthy controls. Anti-islet antigen, anti-islet cell, anti-glutamic acid decarboxylase, and anti-Coxsackievirus-B IgG antibody titers were greater in patients than controls. The majority of autoantibodies tested correlated with Coxsackievirus-B IgG antibodies.Conclusion: Anti-Coxsackievirus-B IgG antibody positivity was associated with autoantibodies related to type 1 diabetes mellitus.Keywords: Coxsackievirus B, type 1 diabetes, autoantibodiesCitation: Hassan HG, Al-Shuwaikh AM, Al-Auqili RKD. Association of Anti-Coxsackie Virus-B IgG with autoantibodies related to type 1 diabetes mellitus. Iraqi JMS. 2022; 20(1): 132-138. doi: 10.22578/IJMS.20.1.17
Keywords: Coxsackievirus B; type 1 diabetes; autoantibodies